Immune cell changes in response to a swimming training session during a 24-h recovery period - Morgado, J. P.; Monteiro, C. P.; Teles, J.; Reis, J. F.; Matias, C.; Seixas, M. T.; Alvim, M. G.; Bourbon, M.; Laires, M. J.; Alves, F. (Applied Physiology, Nutrition, and Metabolism, 2016)
Understanding the impact of training sessions on the immune response is crucial for the adequate periodization of training, to prevent both a negative influence on health and a performance impairment of the athlete. This study evaluated acute systemic immune cell changes in response to an actual swimming session, during a 24-h recovery period, controlling for sex, menstrual cycle phases, maturity, and age group. Competitive swimmers (30 females, 15 ± 1.3 years old; and 35 males, 16.5 ± 2.1 years old) performed a high-intensity training session. Blood samples were collected before, immediately after, 2 h after, and 24 h after exercise. Standard procedures for the assessment of leukogram by automated counting (Coulter LH 750, Beckman) and lymphocytes subsets by flow cytometry (FACS Calibur BD, Biosciences) were used. Subjects were grouped according to competitive age groups and pubertal Tanner stages. Menstrual cycle phase was monitored. The training session induced neutrophilia, lymphopenia, and a low eosinophil count, lasting for at least 2 h, independent of sex and maturity. At 24 h postexercise, the acquired immunity of juniors (15-17 years old), expressed by total lymphocytes and total T lymphocytes (CD3+), was not fully recovered. This should be accounted for when planning a weekly training program. The observed lymphopenia suggests a lower immune surveillance at the end of the session that may depress the immunity of athletes, highlighting the need for extra care when athletes are exposed to aggressive environmental agents such as swimming pools.